ANALISIS BISNIS DAN TREN KONSUMSI MASYARAKAT KABUPATEN BANGKALAN TERHADAP FROZEN FOOD PADA MASA PANDEMI COVID 19 - Sula, Atik Emilia; Chamalinda, Khy'sh Nusri Leapatra (Universitas Islam Balitar, 2021)
The shift in consumer behaviour and food fulfilment by people who initially shopped for fresh good food ingredients during the pandemic is predicted to require fast food with long durability, so this can be an opportunity for developing the food business in the future, especially in the development of the frozen food business. The purpose of this study is to explore the interests and consumption trends of the people of Bangkalan Regency towards frozen food and describe how frozen food business analysis can be developed by MSMEs and home-based culinary business actors during the Covid-19 pandemic. The research methodology used is qualitative, with a phenomenological paradigm approach. Data were collected using questionnaires, group discussion forums (FGD), and in-depth interviews, where all the information was selected by purposive sampling. The results showed an increase in frozen food consumption during the pandemic, extensive business opportunities opened up in the frozen food sector, and frozen food could be an alternative to fulfil food needs during the pandemic. Keywords: Frozen Food Business, Consumption Trends, Covid 19 Pandemic